Analisis Komparatif Kinerja Keuangan Bank Syariah Sebelum Dan Saat Pandemi Covid-19 (Studi Pada Bank Syariah Yang Terdaftar Di OJK) - Yuni Rahmawati; M Agus Salim; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study was to analyze the differences in the performance of Islamic banks before and during the Covid-19 pandemic. The Islamic banks studied in this study are Islamic banks registered with the OJK. There are three variables used in this study, namely Operational Expenses to Operational Income (BOPO), Return On Assets (ROA), and Financing To Deposit Ratio (FDR). This study uses the Paired Sample T-test analysis method to show the results of a paired data study, namely data before the Covid-19 pandemic and during the Covid-19 pandemic. The results of this study indicate that there is no difference in the BOPO of Islamic banks before the Covid-19 pandemic and during the Covid-19 pandemic. There is no difference in the ROA of Islamic banks before the Covid-19 pandemic and during the Covid-19 pandemic. There are differences in the FDR of Islamic banks before the Covid-19 pandemic and during the Covid-19 pandemic. Key Words: BOPO, ROA, FDR